The Influence Of Using Media Trainer Instrumentation For Monitoring System Alarms On The Learning Outcomes Maritime Electrical Cadets - Mulyanto H, Sri; Santoso, Agus Dwi; Harianto, Bambang Bagus (Technium Social Sciences Journal, 2023)
Control and instrumentation engineering education plays a crucial role in preparing DIII Maritime Electrical to face the complexity of control systems in the maritime industry. In an effort to improve the quality of learning, the use of educational technologies such as media trainer instrumentation alarm monitoring systems has become the focus of research. The study aims to investigate the impact of the use of media trainer instrumentation alarm system monitoring on the learning results of the control system of the cadets. Merchant Marine Polytechnic Of Surabaya, as the leading maritime higher education institution in Indonesia, has led in integrating this technology into the learning process. By leveraging the media trainer instrumentation alarm monitoring system, they hope the cadets can gain a deep understanding of the key concepts in system control and monitoring. This research uses a quantitative data analysis approach. The control group followed conventional teaching methods, while the experimental group engaged in learning using this technology. Learning data from both groups, including test scores, tasks, and performance evaluations, were collected and analyzed. The results of this research provide valuable insights for maritime higher education institutions and practitioners in this industry. The use of trainer learning media has a significant impact on the learning outcomes of the experimental class, which reaches a higher level compared to the control class that does not use the trainer (protoboard) learning media in the Control System courses at the ETO Faculty in Merchant Marine Polytechnic Of Surabaya